KERJA SAMA SEKTOR STRATEGIS INDONESIA - DENMARK DALAM ENERGI TERBARUKAN DAN KONSERVASI ENERGI PERIODE 2015-2018 - Anugrah Prasertya Perwida, - (2018)
The Indonesian Government has set a 23% renewable energy mix target by 2025 and a 41% reduction in GHG emissions with International assistance. This is due to increased consumption of fossil energy and the increase of high GHG emissions in the world and also by the people of Indonesia. The effort in realizing the taget has a pull power. The research, entitled "Indonesia-Denmark Strategic Sector Cooperation (SSC) in Renewable Energy and Energy Efficiency". It has a research question of how is Indonesia-Denmark strategic sector cooperation in Renewable Energy and energy efficiency period 2015-2018. The purpose of this research is to understand, to know and ato nalyze the cooperation of strategic sector of Indonesia-Denmark in renewable energy and energy efficiency period 2015-2018. The approach of this research is qualitative. The type of research used is applied and descriptive. The data sources used are primary and secondary data from interviews, library studies and audio-visual recording, as well as data on consumption, conservation, availability and production, modeling and long-term energy planning in Indonesia from the Ministry of Energy and Mineral Resources. Data will be analyzed using the theory of International Cooperation, Bilateral Cooperation Concept, Renewable Energy and Energy Conservation. Based on data analysis, it is concluded that SSC cooperation provides long-term modeling and energy planning such as Sisifos (Stochastic System Adequacy Modeling) modeling and NDC (National Determined Contribution) Roadmap, renewable energy integration aid such as modeling aid for electricity network and improvement technical qualities of micro hydro and wind, as well as energy conservation such as energy conservation at power plants and the development of conservation valuation codes.